2010
DOI: 10.1186/1471-2334-10-27
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HPV infection among Greek women attending a gynecological outpatient clinic

Abstract: BackgroundHuman papillomavirus (HPV) infection is a causative factor for cervical cancer. Early detection of high risk HPV types might help to identify women at high risk of cervical cancer. The aim of the present study was to examine the HPV prevalence and distribution in cervical smears in a sample of Greek women attending a gynecological outpatient clinic and to explore the determinants of the infection.MethodsA total of 225 women were studied. All women underwent a regular gynecological control. 35 HPV typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
23
3
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 42 publications
(51 reference statements)
10
23
3
3
Order By: Relevance
“…All cervical samples were extracted via an automated nucleic acid extraction system (NucliSens easyMAG; Biomerieux, Marcy L'étoile, France). A low-density DNA microarray assay (Clinical Arrays Papillomavirus; Genomica, Madrid, Spain) was used for hybridization of amplified and biotinylated sequences of 450-bp DNA fragments from the L1 region of the HPV virus, which is highly conserved and specific to each HPV genotype [8,13] Statistical analysis was performed with SPSS 16.0 (SPSS, Chicago, IL, USA) and Epi Info 3.5.1 (Centers for Disease Control and Prevention, Atlanta, GA, USA). Intergroup differences were assessed via t and χ 2 tests.…”
Section: Methodsmentioning
confidence: 99%
“…All cervical samples were extracted via an automated nucleic acid extraction system (NucliSens easyMAG; Biomerieux, Marcy L'étoile, France). A low-density DNA microarray assay (Clinical Arrays Papillomavirus; Genomica, Madrid, Spain) was used for hybridization of amplified and biotinylated sequences of 450-bp DNA fragments from the L1 region of the HPV virus, which is highly conserved and specific to each HPV genotype [8,13] Statistical analysis was performed with SPSS 16.0 (SPSS, Chicago, IL, USA) and Epi Info 3.5.1 (Centers for Disease Control and Prevention, Atlanta, GA, USA). Intergroup differences were assessed via t and χ 2 tests.…”
Section: Methodsmentioning
confidence: 99%
“…The result showed a difference of opinion while comparing to studies done by others (Cite Table2).The overall prevalence of HPV was 42.5%in the US (Susan Hariri et al,. 2011) [16] , 13.3% in southeast China (Ye et al 2010) [17] , 15.1% in the UK (Cotton et al 2007) [18] , and 22.7% in Greek population (PetroulaStamatakiet al,2010) [19] . The evaluation of our study showed a lower HPV prevalence in cervical smears compared with the study done by Laikangbam P et al, (2007) [20] in Sikkim and Kulkarni SS et al, (2011) [21] in Karnataka and in Andhra Pradesh (Pavaniet al,.2005) [24] but similar results were found by study done in Uttar Pradesh (Srivastava S et al,2012) [22] and in Eastern India (Dutta S et al,.…”
Section: ) the Statistical Analysismentioning
confidence: 99%
“…Tarkowski et al detected HPV in 64% of 312 adolescent females, more than half of them had multiple HPV infection [13]. In 2010 Stamataki et al detected prevalence of HPV DNA in Greek females aged 16 to 45 year, the highest prevalence 57.1% was found among women aged 16-20 years [14].…”
Section: Discussionmentioning
confidence: 99%